Impact of Toxoplasma gondii infection on human health - Rahman, Taibur; E Gulshan, Jerin; Rahman, Atiqur (Bioresearch Communications, 2021)
Toxoplasmosis is one of the most prevalent infectious disease around the globe and it is caused by the parasite named Toxoplasma gondii. Infections normally lead to asymptomatic parasite persistence in immunocompetent warm-blooded hosts, including up to 30-50% of humans. However, T. gondii infection has also a major medical concern and can lead to life-threatening diseases, after reactivation in immunocompromized individuals, particularly in patients with human immunodeficiency virus/cancer or organ transplant recipients, after vertical transmission to fetuses of pregnant women and by inducing recurrent uveitis in immunocompetent adults. More importantly, T. gondii undergoes stage conversion from its fast-replicating tachyzoite to slow replicating dormant bradyzoite preferentially in the brain and skeletal muscles, and lesser extent in the eye, liver, kidney and lung which enable the parasite to persist for the whole life of an individual. Due to the persistence behavior of the parasite in different parts of human body, T. gondii can develop multiple human diseases with severe clinical symptoms. In this study, we have summarized the association of T. gondii in multiple human diseases for instance Encephalitis, Parkinson’s disease, Schizophrenia, Heart disease, Ocular Toxoplasmosis, Congenital abnormalities, Cancer and Diabetes. This highlights the potential role of T. gondii in developing fatal diseases, particularly in immunocompromised individuals despite having asymptomatic nature of the parasite. Bioresearch Commu. 8(1): 1093-1099, 2022 (January)